Production process of buried cable based on non-metal biomimetic material and cable
By using buried cables prepared with non-metallic bionic materials and composite polythiophene and other materials, traditional cables are solved by the problem of corrosion and electromagnetic interference in underground environments, higher corrosion resistance and electromagnetic shielding effect are achieved, and the service life of the cable is extended.
Patent Information
- Application Number
- CN202510174253.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-05-09
AI Technical Summary
Traditional underground cables are susceptible to electrochemical corrosion, humidity, salt, microorganisms and other factors in underground environments, resulting in a shortened service life and may suffer from electromagnetic interference in complex electromagnetic environments, affecting the quality of signal transmission.
The underground cable production process based on non-metallic bionic materials is adopted, including the use of dopant modified composite polythiophene as the conductor material, combined with crosslinked polyethylene particles, polyurethane foaming agent, silicone rubber, carbon fiber cloth, epoxy resin and boron nitride nanosheets, and cables are prepared through extrusion, drying, melting and molding steps.
The cable material has good corrosion resistance, mechanical strength and electrical insulation properties. It can operate stably in harsh underground environments for a long time, extend the service life of the cable, and reduce signal interference in the electromagnetic environment.
Smart Images

Figure CN119952935A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cable production, in particular to a production process and cable for underground cables based on non-metallic bionic materials. Background Art
[0002] In underground environments, traditional cables are often exposed to a variety of corrosion factors, which significantly shortens their service life. Metal cables are particularly susceptible to electrochemical corrosion in the soil and gradually deteriorate. Natural factors such as underground moisture, salt, and microorganisms can corrode cables. In addition, temperature fluctuations and mechanical stress (for example, caused by soil settlement or geological activities) can also affect the long-term performance of cables. Moisture in the soil can not only directly damage the cable sheath, but also biological factors in the underground environment, such as the decomposition of microorganisms and the growth pressure and even penetration of plant roots, can cause physical damage to the cable. Furthermore, in complex electromagnetic environments, such as near high-voltage transmission lines or communication base stations, traditional cables may also suffer from electromagnetic interference, thereby affecting the quality and stability of signal transmission. In view of this, we propose a production process and cable for underground cables based on non-metallic bionic materials. Summary of the invention
[0003] The purpose of the present invention is to provide a production process and cable for an underground cable based on non-metallic bionic materials, so as to solve the problems raised in the above-mentioned background technology.
[0004] To achieve the above object, the present invention provides a production process for an underground cable based on non-metallic bionic materials, comprising the following steps:
[0005] S1.1, weigh the following raw materials in parts by weight: 5-20 parts by weight of composite polythiophene, 30-60 parts by weight of cross-linked polyethylene particles, 5-15 parts by weight of polyurethane foaming agent, 10-20 parts by weight of silicone rubber, 5-15 parts by weight of carbon fiber cloth, 10-25 parts by weight of epoxy resin, 10-20 parts by weight of phthalic anhydride curing agent, and 5-20 parts by weight of polyolefin particles;
[0006] The composite polythiophene is prepared by modifying polythiophene with a dopant and preparing the polythiophene with a boron nitride nanosheet; the dopant is dodecylbenzenesulfonic acid.
[0007] S1.2, extrude the composite polythiophene through an extruder, set the extruder temperature to 180-220°C, the screw speed to 20-60rpm, and the back pressure to 2-10MPa, to prepare a wire to obtain a conductor;
[0008] Composite polythiophenes are generally lighter than traditional metals (such as copper or aluminum), which reduces the overall weight of the cable, thereby reducing transportation and installation costs. At the same time, these materials tend to have good mechanical strength and can withstand a certain amount of tensile force and pressure. The underground environment may contain moisture, chemicals in the soil, and microorganisms, all of which may cause corrosion of metal conductors. Composite polythiophenes have better corrosion resistance and can effectively extend the service life of cables. Polythiophenes have good flexibility and ductility, making cables easier to bend and adjust during laying, especially in complex terrain or limited space. Some polythiophenes are recyclable, and the energy consumption and pollution in the production process are relatively low, which meets the requirements of sustainable development.
[0009] S1.3, select cross-linked polyethylene particles with a diameter of 5 mm, and dry the cross-linked polyethylene particles; heat the extruder to 150-200°C, add the dried cross-linked polyethylene particles into the hopper of the extruder, and push the cross-linked polyethylene particles forward by rotating the screw, and melt them at high temperature;
[0010] The molten cross-linked polyethylene particles are extruded through a die to form a uniform insulation layer wrapped around the conductor to obtain a power transmission cable core, with the insulation layer coverage rate being 20% to 30%;
[0011] Cross-linked polyethylene has a three-dimensional mesh structure, which prevents it from decomposing or carbonizing in high temperature environments. The long-term working temperature can reach 90°C and the thermal life can reach 40 years. At the same time, it maintains the good insulation properties of the original polyethylene, and the insulation resistance is further increased. Its dielectric loss tangent is very small and is not greatly affected by temperature. It can provide stable insulation performance under different temperature conditions, ensuring that the cable reduces energy loss during power transmission and improves power transmission efficiency. Cross-linked polyethylene has strong acid, alkali and oil resistance, and its combustion products are mainly water and carbon dioxide, which have less harm to the environment and meet the requirements of modern fire safety. It is also lighter than polyvinyl chloride insulated cables, has a smaller diameter, is easy to install and lay, and has simple accessory joints.
[0012] S1.4. After preheating the silicone rubber, inject it into the mold, then put the conductor and the insulation layer wrapped with the filling material into the mold, and heat the silicone rubber to solidify and form a uniform water-blocking and flame-retardant layer with an overlap rate of 20% to 30%, which is wrapped around the power transmission cable core;
[0013] Silicone rubber has good flame retardancy, can effectively prevent the spread of flames, protect the conductor and insulation layer inside the cable, and can also effectively prevent moisture penetration, protect the electrical components inside the cable from moisture erosion, and extend the service life of the cable; Silicone rubber has good weather resistance and corrosion resistance, can operate stably for a long time in harsh underground environments, and also has certain elasticity and compressive strength, which can provide additional mechanical protection for the cable, helping to prevent the cable from being damaged when subjected to external pressure or impact.
[0014] S1.5. Select a polyurethane foaming agent with a foaming rate of 40 times as the filling material, inject it into the water-blocking and flame-retardant layer through a special injection gun, and let the foam expand naturally and completely solidify;
[0015] Polyurethane foam has good insulation properties, which can effectively prevent current leakage and protect the conductor and insulation layer of the cable, which is especially important for buried cables because they need to maintain stable electrical properties in harsh underground environments; in addition, polyurethane foam has good corrosion resistance and can resist erosion by chemicals, moisture and microorganisms in the soil, which helps to extend the service life of buried cables. It also has certain elasticity and compressive strength, which can provide additional mechanical protection for the cable, which helps to prevent the cable from being damaged when subjected to external pressure or impact; polyurethane foam has a low density and light weight, which is very beneficial for the laying and installation of buried cables.
[0016] S1.6. Use an electric stirrer to mix the epoxy resin and phthalic anhydride curing agent evenly until the color is consistent and there is no obvious stratification. Soak the carbon fiber cloth in the mixed resin to ensure that each fiber is completely soaked in the resin to obtain an armor layer. Use a spiral winding method to tightly and evenly wrap the resin-impregnated carbon fiber cloth on the water-blocking and flame-retardant layer.
[0017] Carbon fiber has extremely high strength, and its tensile strength is much higher than many traditional metal materials (such as steel, etc.). When the cable is pulled or bent by external forces, it can effectively resist these external forces and protect the internal structure of the cable from damage; at the same time, the composite material formed after the epoxy resin is cured has good rigidity and impact resistance, which helps to further enhance the protection effect. Carbon fiber itself has good chemical stability and is not easy to react with chemicals in the external environment. Epoxy resin also has certain chemical corrosion resistance. The armor layer formed by the combination of the two can effectively protect the cable from external chemicals (such as acid rain, corrosive substances in the soil, etc.) and extend the service life of the cable. Carbon fiber has a certain conductivity, but when it is fully infiltrated and cured by epoxy resin, the entire composite material can play a certain electromagnetic shielding role, reducing the influence of external electromagnetic interference on the internal signal transmission of the cable; at the same time, the insulation performance of epoxy resin can also ensure the electrical insulation inside the cable.
[0018] S1.7, select polyolefin particles with a particle size of 100 μm, and dry the polyolefin particles at a drying temperature of 60-100° C. for a drying time of 2-6 hours;
[0019] The extruder is heated to 180-250°C, the dried polyolefin particles are added into the hopper of the extruder, and the polyolefin particles are pushed forward by the rotation of the screw. The screw speed is set at 20-50rpm, the torque is set at 40-60N·m, the back pressure is set at 2-10MPa, and melted at high temperature; the molten polyolefin particles are extruded through the die to form a uniform outer sheath layer, which is wrapped around the armor layer.
[0020] Polyolefin materials have excellent electrical insulation properties and can effectively isolate the impact of the external environment on the internal conductors of the cable, ensuring the safety and reliability of power transmission; at the same time, they have good resistance to most acids, alkalis and organic solvents, and have good aging resistance. They can maintain the stability of their physical and chemical properties during long-term use and extend the service life of the cable; polyolefins generally have good flexibility and tensile strength, and can withstand a certain degree of bending and stretching without breaking, which helps to improve the overall durability of the cable, and compared with some other plastics, polyolefins have a lower water absorption rate, which helps prevent moisture from penetrating into the cable, thereby reducing the risk of electrical failures caused by moisture.
[0021] Preferably, in S1.3, the drying temperature is 80-100°C and the drying time is 2-4h.
[0022] Preferably, in S1.3, the screw speed is set at 20-60 rpm, the torque is set at 10-50 N·m, and the back pressure is set at 2-10 MPa.
[0023] Preferably, in S1.5, the preheating temperature of the silicone rubber is set to 60-100°C, and the preheating time is 10-30 minutes; the heating temperature for curing the silicone rubber is 120-180°C, and the heating time is 1-3 hours.
[0024] Preferably, in S1.6, the speed of the electric stirrer is set to 200-400 rpm, and the stirring time is 15-30 min.
[0025] Preferably, the composite polythiophene is prepared as follows:
[0026] S1.1, weigh the following raw materials in parts by weight: 50-75 parts by weight of polythiophene, 1-10 parts by weight of dopant, 1-10 parts by weight of boron nitride nanosheets, and 10-20 parts by weight of N-methylpyrrolidone;
[0027] S1.2, respectively add polythiophene and dopant into N-methylpyrrolidone, use magnetic stirrer to fully disperse, stirring speed is 300-500rpm, stirring time is 0.5-1h, obtain dispersed polythiophene and dopant;
[0028] Add the dispersed polythiophene to the dopant at 20-30 drops / minute, stirring continuously to ensure uniform mixing, to obtain the doped polythiophene;
[0029] Dopants can introduce additional charge carriers (such as holes or electrons) into polythiophene, thereby significantly improving the conductivity of the material. At the same time, they can adjust the energy level structure of polythiophene, thereby optimizing its light absorption characteristics, photoelectric conversion efficiency and carrier mobility. Dopants can not only improve conductivity, but also enhance the mechanical strength and toughness of the material through interactions with polymer chains, which helps to extend the service life of the material in practical applications.
[0030] Dopants can improve the thermal stability of polythiophene, allowing it to maintain good performance over a wider temperature range; sometimes they affect the melting point, glass transition temperature (Tg) and other physical properties of the polymer, thereby changing the processing window of the material. Appropriate doping can make the material easier to process while maintaining the required performance; through doping, polythiophene's tolerance to humidity, oxygen and other environmental factors can be improved, thereby extending the service life of the material in harsh environments, which is particularly important for applications such as buried cables that are exposed to the natural environment for a long time.
[0031] S1.3, adding boron nitride nanosheets to N-methylpyrrolidone, and then adding to the doped polythiophene, using ultrasound to disperse, and continuously stirring at a stirring speed of 400-600 rpm for 1-5 hours to obtain a mixture;
[0032] Boron nitride nanosheets have excellent thermal stability and chemical inertness. Adding them can significantly improve the thermal stability of polythiophene, allowing the composite material to maintain good performance in a wider temperature range. At the same time, as a two-dimensional material, it has high strength and stiffness and can be evenly dispersed in the polymer matrix to form a reinforced network, thereby improving the tensile strength, toughness and impact resistance of the composite material.
[0033] Although polythiophene is a conductive polymer, sometimes its electrical insulation properties need to be improved locally or as a whole. Boron nitride nanosheets are a good electrical insulating material that can provide better electrical insulation without affecting the conductive area. It can form a tightly arranged layered structure, which helps to improve the barrier properties of the composite material to gases and liquids. In addition, the chemical inertness of boron nitride nanosheets can help improve the corrosion resistance of the composite material, especially in a humid or corrosive environment, protecting the internal conductive polymer from damage. Boron nitride nanosheets are a non-toxic and environmentally friendly material. Their addition will not cause pollution to the environment and meet the requirements of sustainable development.
[0034] S1.4. Wash the mixture with 50-70% ethanol to remove unreacted dopants and impurities; then dry the mixture to obtain composite polythiophene.
[0035] Preferably, in S1.2, the continuous stirring speed is 400-800 rpm, and the stirring time is 3-6 h.
[0036] Preferably, in S1.3, the ultrasonic power is set to 200-400W, and the ultrasonic time is set to 0.5-1h.
[0037] Preferably, in S1.4, the drying temperature is 50-80°C and the drying time is 2-3h.
[0038] On the other hand, the present invention provides an underground cable based on non-metallic bionic materials, which is made by the production process of the underground cable based on non-metallic bionic materials described in any one of the above-mentioned items. The underground cable includes, from the inside to the outside, a power transmission cable core, a filling material, a water-blocking and flame-retardant layer, an armor layer, and an outer protective tape layer; the power transmission cable core includes, from the inside to the outside, a conductor and an insulation layer.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. In the production process and cable of the buried cable based on non-metallic bionic materials, dopants are used to modify polythiophene, because the dopants can introduce additional charge carriers (such as holes or electrons) into polythiophene, thereby significantly improving the conductivity of the material. The dopants can not only improve the conductivity, but also enhance the mechanical strength and toughness of the material through the interaction with the polymer chain, which helps to extend the service life of the material in practical applications; in addition, the tolerance of polythiophene to humidity, oxygen and other environmental factors can be improved, thereby extending the service life of the material in harsh environments.
[0041] 2. Boron nitride nanosheets are added to the production process and cable of the buried cable based on non-metallic bionic materials because of their excellent thermal stability and chemical inertness. Addition can significantly improve the thermal stability of polythiophene, so that the composite material can maintain good performance in a wider temperature range; at the same time, as a two-dimensional material, it has high strength and stiffness, and can be evenly dispersed in the polymer matrix to form a reinforced network, thereby improving the tensile strength, toughness and impact resistance of the composite material; in addition, the chemical inertness of boron nitride nanosheets can help improve the corrosion resistance of the composite material, especially in a humid environment or one containing corrosive media, protecting the internal conductive polymer from damage. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a schematic diagram of the structure of an underground cable.
[0043] Illustration
[0044] 1. Power transmission cable core; 11. Conductor; 12. Insulation layer; 2. Filling material; 3. Water-blocking and flame-retardant layer; 4. Armor layer; 5. Outer protective tape layer. DETAILED DESCRIPTION
[0045] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0046] The buried cable based on non-metallic bionic materials of the present invention comprises, from inside to outside, a power transmission cable core 1, a filling material 2, a water-blocking and flame-retardant layer 3, an armor layer 4, and an outer protective tape layer 5; the power transmission cable core 1 comprises, from inside to outside, a conductor 11 and an insulating layer 12.
[0047] The production process of underground cables based on non-metallic bionic materials includes the following steps:
[0048] S1.1, weigh the following raw materials in parts by weight: 5-20 parts by weight of composite polythiophene, 30-60 parts by weight of cross-linked polyethylene particles, 5-15 parts by weight of polyurethane foaming agent, 10-20 parts by weight of silicone rubber, 5-15 parts by weight of carbon fiber cloth, 10-25 parts by weight of epoxy resin, 10-20 parts by weight of phthalic anhydride curing agent, and 5-20 parts by weight of polyolefin particles;
[0049] The composite polythiophene is prepared by modifying polythiophene with a dopant and preparing the polythiophene with a boron nitride nanosheet; the dopant is dodecylbenzenesulfonic acid.
[0050] S1.2, extrude the composite polythiophene through an extruder, set the extruder temperature to 180-220°C, the screw speed to 20-60rpm, and the back pressure to 2-10MPa, to prepare a wire to obtain a conductor 11;
[0051] S1.3, select cross-linked polyethylene particles with a diameter of 5 mm, dry the cross-linked polyethylene particles at a drying temperature of 80-100°C and a drying time of 2-4 hours; heat the extruder to 150-200°C, add the dried cross-linked polyethylene particles into the hopper of the extruder, push the cross-linked polyethylene particles forward by rotating the screw, the screw speed is 20-60rpm, the torque is 10-50N·m, the back pressure is 2-10MPa, and melt at high temperature;
[0052] The molten cross-linked polyethylene particles are extruded through a die to form a uniform insulating layer 12 which is wrapped around the conductor 11 to obtain a power transmission cable core 1, wherein the overlapping rate of the insulating layer 12 is 20% to 30%;
[0053] S1.4, preheat the silicone rubber at a temperature of 60-100°C for 10-30 minutes, inject it into the mold, and then put the conductor and the insulating layer wrapped with the filling material into the mold, and heat it at a temperature of 120-180°C for 1-3 hours to cure the silicone rubber and form a uniform water-blocking and flame-retardant layer 3 with an overlap rate of 20% to 30%, which is wrapped around the power transmission cable core 1;
[0054] S1.5, select a polyurethane foaming agent with a foaming rate of 40 times as the filling material 2, inject it into the water-blocking and flame-retardant layer 3 through a special glue injection gun, and let the foam expand naturally and completely solidify;
[0055] S1.6. Use an electric stirrer to mix the epoxy resin and phthalic anhydride curing agent evenly at a speed of 200-400 rpm for 15-30 minutes until the color is consistent and there is no obvious stratification phenomenon. Soak the carbon fiber cloth in the mixed resin to ensure that each fiber is completely soaked in the resin to obtain the armor layer 4. Use a spiral winding method to tightly and evenly wrap the resin-impregnated carbon fiber cloth on the water-blocking and flame-retardant layer 3;
[0056] S1.7, selecting polyolefin particles with a particle size of 100 μm, and drying the polyolefin particles at a drying temperature of 60-100° C. for a drying time of 2-6 hours;
[0057] The extruder is heated to 180-250°C, and the dried polyolefin particles are added into the hopper of the extruder. The polyolefin particles are pushed forward by the rotation of the screw. The screw speed is 20-50rpm, the torque is 40-60N·m, the back pressure is 2-10MPa, and the polyolefin particles are melted at high temperature. The molten polyolefin particles are extruded through the die to form a uniform outer sheath layer 5, which is wrapped around the armor layer 4.
[0058] Preferably, the composite polythiophene is prepared as follows:
[0059] S1.1, weigh the following raw materials in parts by weight: 50-75 parts by weight of polythiophene, 1-10 parts by weight of dopant, 1-10 parts by weight of boron nitride nanosheets, and 10-20 parts by weight of N-methylpyrrolidone;
[0060] S1.2, respectively add polythiophene and dopant into N-methylpyrrolidone, use magnetic stirrer to fully disperse, stirring speed is 300-500rpm, stirring time is 0.5-1h, obtain dispersed polythiophene and dopant;
[0061] Add the dispersed polythiophene to the dopant at a rate of 20-30 drops / minute, and continue stirring to ensure uniform mixing at a stirring speed of 400-800 rpm for 3-6 hours to obtain doped polythiophene;
[0062] S1.3, adding boron nitride nanosheets to N-methylpyrrolidone, and then adding to the doped polythiophene, using ultrasound to disperse, the ultrasound power is 200-400W, the ultrasound time is 0.5-1h, and stirring is continued, the stirring speed is 400-600rpm, and the stirring time is 1-5h to obtain a mixture;
[0063] S1.4. Wash the mixture with 50-70% ethanol to remove unreacted dopants and impurities; then dry the mixture at a temperature of 50-80°C for 2-3 hours to obtain composite polythiophene.
[0064] Embodiment 1: A production process of an underground cable based on non-metallic bionic materials and a cable, comprising the following steps:
[0065] The buried cable structure based on non-metallic bionic materials includes, from the inside to the outside, a power transmission cable core 1, a filling material 2, a water-blocking and flame-retardant layer 3, an armor layer 4, and an outer protective tape layer 5; the power transmission cable core 1 includes, from the inside to the outside, a conductor 11 and an insulating layer 12.
[0066] The production process of underground cables based on non-metallic bionic materials includes the following steps:
[0067] S1.1, weigh the following raw materials in parts by weight: 12 parts by weight of composite polythiophene, 45 parts by weight of cross-linked polyethylene particles, 10 parts by weight of polyurethane foaming agent, 15 parts by weight of silicone rubber, 10 parts by weight of carbon fiber cloth, 17 parts by weight of epoxy resin, 15 parts by weight of phthalic anhydride curing agent, and 12 parts by weight of polyolefin particles;
[0068] S1.2, extrude the composite polythiophene through an extruder, set the extruder temperature to 220° C., the screw speed to 50 rpm, and the back pressure to 6 MPa, to prepare a wire to obtain a conductor 11;
[0069] S1.3, select cross-linked polyethylene particles with a diameter of 5 mm, dry the cross-linked polyethylene particles at a drying temperature of 100°C and a drying time of 3 hours; heat the extruder to 180°C, add the dried cross-linked polyethylene particles into the hopper of the extruder, push the cross-linked polyethylene particles forward by rotating the screw, the screw speed is 60rpm, the torque is 40N·m, the back pressure is 6MPa, and melt at high temperature;
[0070] The molten cross-linked polyethylene particles are extruded through a die to form a uniform insulating layer 12 which is wrapped around the conductor 11 to obtain a power transmission cable core 1, wherein the overlapping rate of the insulating layer 12 is 30%;
[0071] S1.4, preheat the silicone rubber at 80°C for 30 minutes, inject it into the mold, and then put the conductor and the insulating layer wrapped with the filling material into the mold, and heat it at 180°C for 3 hours to cure the silicone rubber to form a uniform water-blocking and flame-retardant layer 3 with an overlap rate of 30%, which is wrapped around the power transmission cable core 1;
[0072] S1.5. Select a polyurethane foaming agent with a foaming rate of 40 times as the filling material 2, inject it into the water-blocking and flame-retardant layer 3 through a special glue injection gun, and let the foam expand naturally and completely solidify;
[0073] S1.6. Use an electric stirrer to mix the epoxy resin and phthalic anhydride curing agent evenly at a speed of 300 rpm for 30 minutes until the color is consistent and there is no obvious stratification phenomenon. Soak the carbon fiber cloth in the mixed resin to ensure that each fiber is completely soaked in the resin to obtain the armor layer 4. Use a spiral winding method to tightly and evenly wrap the resin-impregnated carbon fiber cloth on the water-blocking and flame-retardant layer 3;
[0074] S1.7, selecting polyolefin particles with a particle size of 100 μm, and drying the polyolefin particles at a drying temperature of 80° C. for a drying time of 3 h;
[0075] The extruder is heated to 200°C, and the dried polyolefin particles are added into the hopper of the extruder. The polyolefin particles are pushed forward by the rotation of the screw. The screw speed is 40rpm, the torque is 50N·m, the back pressure is 6MPa, and they are melted at high temperature. The molten polyolefin particles are extruded through the die to form a uniform outer sheath layer 5, which is wrapped around the armor layer 4.
[0076] The composite polythiophene is prepared as follows:
[0077] S1.1, weigh the following raw materials in parts by weight: 60 parts by weight of polythiophene, 3 parts by weight of dodecylbenzenesulfonic acid, 5 parts by weight of boron nitride nanosheets, and 15 parts by weight of N-methylpyrrolidone;
[0078] S1.2, polythiophene and dodecylbenzene sulfonic acid were added to N-methylpyrrolidone respectively, and fully dispersed using a magnetic stirrer at a stirring speed of 400 rpm for 1 h to obtain dispersed polythiophene and dodecylbenzene sulfonic acid;
[0079] The dispersed polythiophene was added into dodecylbenzene sulfonic acid at a rate of 20 drops / min, and stirring was continued to ensure uniform mixing. The stirring speed was 600 rpm and the stirring time was 5 h to obtain doped polythiophene;
[0080] S1.3, adding boron nitride nanosheets to N-methylpyrrolidone, and then adding to the doped polythiophene, using ultrasound to disperse, the ultrasonic power is 300 W, the ultrasonic time is 1 hour, and stirring is continued, the stirring speed is 400 rpm, and the stirring time is 3 hours to obtain a mixture;
[0081] S1.4. Wash the mixture with 70% ethanol to remove unreacted dodecylbenzenesulfonic acid and impurities; then dry it at 80°C for 3 hours to obtain composite polythiophene.
[0082] Embodiment 2: A production process of an underground cable based on non-metallic bionic materials and a cable, comprising the following steps:
[0083] The buried cable structure based on non-metallic bionic materials includes, from the inside to the outside, a power transmission cable core 1, a filling material 2, a water-blocking and flame-retardant layer 3, an armor layer 4, and an outer protective tape layer 5; the power transmission cable core 1 includes, from the inside to the outside, a conductor 11 and an insulating layer 12.
[0084] The production process of underground cables based on non-metallic bionic materials includes the following steps:
[0085] S1.1, weigh the following raw materials in parts by weight: 12 parts by weight of composite polythiophene, 45 parts by weight of cross-linked polyethylene particles, 10 parts by weight of polyurethane foaming agent, 15 parts by weight of silicone rubber, 10 parts by weight of carbon fiber cloth, 17 parts by weight of epoxy resin, 15 parts by weight of phthalic anhydride curing agent, and 12 parts by weight of polyolefin particles;
[0086] S1.2, extrude the composite polythiophene through an extruder, set the extruder temperature to 220° C., the screw speed to 50 rpm, and the back pressure to 6 MPa, to prepare a wire to obtain a conductor 11;
[0087] S1.3, select cross-linked polyethylene particles with a diameter of 5 mm, dry the cross-linked polyethylene particles at a drying temperature of 100°C and a drying time of 3 hours; heat the extruder to 180°C, add the dried cross-linked polyethylene particles into the hopper of the extruder, push the cross-linked polyethylene particles forward by rotating the screw, the screw speed is 60rpm, the torque is 40N·m, the back pressure is 6MPa, and melt at high temperature;
[0088] The molten cross-linked polyethylene particles are extruded through a die to form a uniform insulating layer 12 which is wrapped around the conductor 11 to obtain a power transmission cable core 1, wherein the overlapping rate of the insulating layer 12 is 30%;
[0089] S1.4, preheat the silicone rubber at 80°C for 30 minutes, inject it into the mold, and then put the conductor and the insulating layer wrapped with the filling material into the mold, and heat it at 180°C for 3 hours to cure the silicone rubber to form a uniform water-blocking and flame-retardant layer 3 with an overlap rate of 30%, which is wrapped around the power transmission cable core 1;
[0090] S1.5, select a polyurethane foaming agent with a foaming rate of 40 times as the filling material 2, inject it into the water-blocking and flame-retardant layer 3 through a special glue injection gun, and let the foam expand naturally and completely solidify;
[0091] S1.6. Use an electric stirrer to mix the epoxy resin and phthalic anhydride curing agent evenly at a speed of 300 rpm for 30 minutes until the color is consistent and there is no obvious stratification phenomenon. Soak the carbon fiber cloth in the mixed resin to ensure that each fiber is completely soaked in the resin to obtain the armor layer 4. Use a spiral winding method to tightly and evenly wrap the resin-impregnated carbon fiber cloth on the water-blocking and flame-retardant layer 3;
[0092] S1.7, selecting polyolefin particles with a particle size of 100 μm, and drying the polyolefin particles at a drying temperature of 80° C. for a drying time of 3 h;
[0093] The extruder is heated to 200°C, and the dried polyolefin particles are added into the hopper of the extruder. The polyolefin particles are pushed forward by the rotation of the screw. The screw speed is 40rpm, the torque is 50N·m, the back pressure is 6MPa, and they are melted at high temperature. The molten polyolefin particles are extruded through the die to form a uniform outer sheath layer 5, which is wrapped around the armor layer 4.
[0094] The composite polythiophene is prepared as follows:
[0095] S1.1, weigh the following raw materials in parts by weight: 60 parts by weight of polythiophene, 5 parts by weight of dodecylbenzenesulfonic acid, 5 parts by weight of boron nitride nanosheets, and 15 parts by weight of N-methylpyrrolidone;
[0096] S1.2, polythiophene and dodecylbenzene sulfonic acid were added to N-methylpyrrolidone respectively, and fully dispersed using a magnetic stirrer at a stirring speed of 400 rpm for 1 h to obtain dispersed polythiophene and dodecylbenzene sulfonic acid;
[0097] The dispersed polythiophene was added into dodecylbenzene sulfonic acid at a rate of 20 drops / min, and stirring was continued to ensure uniform mixing. The stirring speed was 600 rpm and the stirring time was 5 h to obtain doped polythiophene;
[0098] S1.3, adding boron nitride nanosheets to N-methylpyrrolidone, and then adding to the doped polythiophene, using ultrasound to disperse, the ultrasonic power is 300 W, the ultrasonic time is 1 hour, and stirring is continued, the stirring speed is 400 rpm, and the stirring time is 3 hours to obtain a mixture;
[0099] S1.4. Wash the mixture with 70% ethanol to remove unreacted dodecylbenzenesulfonic acid and impurities; then dry it at 80°C for 3 hours to obtain composite polythiophene.
[0100] Embodiment 3: A production process of an underground cable based on non-metallic bionic materials and a cable, comprising the following steps:
[0101] The buried cable structure based on non-metallic bionic materials includes, from the inside to the outside, a power transmission cable core 1, a filling material 2, a water-blocking and flame-retardant layer 3, an armor layer 4, and an outer protective tape layer 5; the power transmission cable core 1 includes, from the inside to the outside, a conductor 11 and an insulating layer 12.
[0102] The production process of underground cables based on non-metallic bionic materials includes the following steps:
[0103] S1.1, weigh the following raw materials in parts by weight: 12 parts by weight of composite polythiophene, 45 parts by weight of cross-linked polyethylene particles, 10 parts by weight of polyurethane foaming agent, 15 parts by weight of silicone rubber, 10 parts by weight of carbon fiber cloth, 17 parts by weight of epoxy resin, 15 parts by weight of phthalic anhydride curing agent, and 12 parts by weight of polyolefin particles;
[0104] S1.2, extrude the composite polythiophene through an extruder, set the extruder temperature to 220° C., the screw speed to 50 rpm, and the back pressure to 6 MPa, to prepare a wire to obtain a conductor 11;
[0105] S1.3, select cross-linked polyethylene particles with a diameter of 5 mm, dry the cross-linked polyethylene particles at a drying temperature of 100°C and a drying time of 3 hours; heat the extruder to 180°C, add the dried cross-linked polyethylene particles into the hopper of the extruder, push the cross-linked polyethylene particles forward by rotating the screw, the screw speed is 60rpm, the torque is 40N·m, the back pressure is 6MPa, and melt at high temperature;
[0106] The molten cross-linked polyethylene particles are extruded through a die to form a uniform insulating layer 12 which is wrapped around the conductor 11 to obtain a power transmission cable core 1, wherein the overlapping rate of the insulating layer 12 is 30%;
[0107] S1.4, preheat the silicone rubber at 80°C for 30 minutes, inject it into the mold, and then put the conductor and the insulating layer wrapped with the filling material into the mold, and heat it at 180°C for 3 hours to cure the silicone rubber to form a uniform water-blocking and flame-retardant layer 3 with an overlap rate of 30%, which is wrapped around the power transmission cable core 1;
[0108] S1.5. Select a polyurethane foaming agent with a foaming rate of 40 times as the filling material 2, inject it into the water-blocking and flame-retardant layer 3 through a special glue injection gun, and let the foam expand naturally and completely solidify;
[0109] S1.6. Use an electric stirrer to mix the epoxy resin and phthalic anhydride curing agent evenly at a speed of 300 rpm for 30 minutes until the color is consistent and there is no obvious stratification phenomenon. Soak the carbon fiber cloth in the mixed resin to ensure that each fiber is completely soaked in the resin to obtain the armor layer 4. Use a spiral winding method to tightly and evenly wrap the resin-impregnated carbon fiber cloth on the water-blocking and flame-retardant layer 3;
[0110] S1.7, selecting polyolefin particles with a particle size of 100 μm, and drying the polyolefin particles at a drying temperature of 80° C. for a drying time of 3 h;
[0111] The extruder is heated to 200°C, and the dried polyolefin particles are added into the hopper of the extruder. The polyolefin particles are pushed forward by the rotation of the screw. The screw speed is 40rpm, the torque is 50N·m, the back pressure is 6MPa, and they are melted at high temperature. The molten polyolefin particles are extruded through the die to form a uniform outer sheath layer 5, which is wrapped around the armor layer 4.
[0112] The composite polythiophene is prepared as follows:
[0113] S1.1, weigh the following raw materials in parts by weight: 60 parts by weight of polythiophene, 8 parts by weight of dodecylbenzenesulfonic acid, 5 parts by weight of boron nitride nanosheets, and 15 parts by weight of N-methylpyrrolidone;
[0114] S1.2, polythiophene and dodecylbenzene sulfonic acid were added to N-methylpyrrolidone respectively, and fully dispersed using a magnetic stirrer at a stirring speed of 400 rpm for 1 h to obtain dispersed polythiophene and dodecylbenzene sulfonic acid;
[0115] The dispersed polythiophene was added into dodecylbenzene sulfonic acid at a rate of 20 drops / min, and stirring was continued to ensure uniform mixing. The stirring speed was 600 rpm and the stirring time was 5 h to obtain doped polythiophene;
[0116] S1.3, adding boron nitride nanosheets to N-methylpyrrolidone, and then adding to the doped polythiophene, using ultrasound to disperse, the ultrasonic power is 300 W, the ultrasonic time is 1 hour, and stirring is continued, the stirring speed is 400 rpm, and the stirring time is 3 hours to obtain a mixture;
[0117] S1.4. Wash the mixture with 70% ethanol to remove unreacted dodecylbenzenesulfonic acid and impurities; then dry it at 80°C for 3 hours to obtain composite polythiophene.
[0118] Embodiment 4: A production process of an underground cable based on non-metallic bionic materials and a cable, comprising the following steps:
[0119] The buried cable structure based on non-metallic bionic materials includes, from the inside to the outside, a power transmission cable core 1, a filling material 2, a water-blocking and flame-retardant layer 3, an armor layer 4, and an outer protective tape layer 5; the power transmission cable core 1 includes, from the inside to the outside, a conductor 11 and an insulating layer 12.
[0120] The production process of underground cables based on non-metallic bionic materials includes the following steps:
[0121] S1.1, weigh the following raw materials in parts by weight: 12 parts by weight of composite polythiophene, 45 parts by weight of cross-linked polyethylene particles, 10 parts by weight of polyurethane foaming agent, 15 parts by weight of silicone rubber, 10 parts by weight of carbon fiber cloth, 17 parts by weight of epoxy resin, 15 parts by weight of phthalic anhydride curing agent, and 12 parts by weight of polyolefin particles;
[0122] S1.2, extrude the composite polythiophene through an extruder, set the extruder temperature to 220° C., the screw speed to 50 rpm, and the back pressure to 6 MPa, to prepare a wire to obtain a conductor 11;
[0123] S1.3, select cross-linked polyethylene particles with a diameter of 5 mm, dry the cross-linked polyethylene particles at a drying temperature of 100°C and a drying time of 3 hours; heat the extruder to 180°C, add the dried cross-linked polyethylene particles into the hopper of the extruder, push the cross-linked polyethylene particles forward by rotating the screw, the screw speed is 60rpm, the torque is 40N·m, the back pressure is 6MPa, and melt at high temperature;
[0124] The molten cross-linked polyethylene particles are extruded through a die to form a uniform insulating layer 12 which is wrapped around the conductor 11 to obtain a power transmission cable core 1, wherein the overlapping rate of the insulating layer 12 is 30%;
[0125] S1.4, preheat the silicone rubber at 80°C for 30 minutes, inject it into the mold, and then put the conductor and the insulating layer wrapped with the filling material into the mold, and heat it at 180°C for 3 hours to cure the silicone rubber to form a uniform water-blocking and flame-retardant layer 3 with an overlap rate of 30%, which is wrapped around the power transmission cable core 1;
[0126] S1.5. Select a polyurethane foaming agent with a foaming rate of 40 times as the filling material 2, inject it into the water-blocking and flame-retardant layer 3 through a special glue injection gun, and let the foam expand naturally and completely solidify;
[0127] S1.6. Use an electric stirrer to mix the epoxy resin and phthalic anhydride curing agent evenly at a speed of 300 rpm for 30 minutes until the color is consistent and there is no obvious stratification phenomenon. Soak the carbon fiber cloth in the mixed resin to ensure that each fiber is completely soaked in the resin to obtain the armor layer 4. Use a spiral winding method to tightly and evenly wrap the resin-impregnated carbon fiber cloth on the water-blocking and flame-retardant layer 3;
[0128] S1.7, selecting polyolefin particles with a particle size of 100 μm, and drying the polyolefin particles at a drying temperature of 80° C. for a drying time of 3 h;
[0129] The extruder is heated to 200°C, and the dried polyolefin particles are added into the hopper of the extruder. The polyolefin particles are pushed forward by the rotation of the screw. The screw speed is 40rpm, the torque is 50N·m, the back pressure is 6MPa, and they are melted at high temperature. The molten polyolefin particles are extruded through the die to form a uniform outer sheath layer 5, which is wrapped around the armor layer 4.
[0130] The composite polythiophene is prepared as follows:
[0131] S1.1, weigh the following raw materials in parts by weight: 50 parts by weight of polythiophene, 4 parts by weight of dodecylbenzenesulfonic acid, 5 parts by weight of boron nitride nanosheets, and 15 parts by weight of N-methylpyrrolidone;
[0132] S1.2, polythiophene and dodecylbenzene sulfonic acid were added to N-methylpyrrolidone respectively, and fully dispersed using a magnetic stirrer at a stirring speed of 400 rpm for 1 h to obtain dispersed polythiophene and dodecylbenzene sulfonic acid;
[0133] The dispersed polythiophene was added into dodecylbenzene sulfonic acid at a rate of 20 drops / min, and stirring was continued to ensure uniform mixing. The stirring speed was 600 rpm and the stirring time was 5 h to obtain doped polythiophene;
[0134] S1.3, adding boron nitride nanosheets to N-methylpyrrolidone, and then adding to the doped polythiophene, using ultrasound to disperse, the ultrasonic power is 300 W, the ultrasonic time is 1 hour, and stirring is continued, the stirring speed is 400 rpm, and the stirring time is 3 hours to obtain a mixture;
[0135] S1.4. Wash the mixture with 70% ethanol to remove unreacted dodecylbenzenesulfonic acid and impurities; then dry it at 80°C for 3 hours to obtain composite polythiophene.
[0136] Embodiment 5: A production process of an underground cable based on non-metallic bionic materials and a cable, comprising the following steps:
[0137] The buried cable structure based on non-metallic bionic materials includes, from the inside to the outside, a power transmission cable core 1, a filling material 2, a water-blocking and flame-retardant layer 3, an armor layer 4, and an outer protective tape layer 5; the power transmission cable core 1 includes, from the inside to the outside, a conductor 11 and an insulating layer 12.
[0138] The production process of underground cables based on non-metallic bionic materials includes the following steps:
[0139] S1.1, weigh the following raw materials in parts by weight: 12 parts by weight of composite polythiophene, 45 parts by weight of cross-linked polyethylene particles, 10 parts by weight of polyurethane foaming agent, 15 parts by weight of silicone rubber, 10 parts by weight of carbon fiber cloth, 17 parts by weight of epoxy resin, 15 parts by weight of phthalic anhydride curing agent, and 12 parts by weight of polyolefin particles;
[0140] S1.2, extrude the composite polythiophene through an extruder, set the extruder temperature to 220° C., the screw speed to 50 rpm, and the back pressure to 6 MPa, to prepare a wire to obtain a conductor 11;
[0141] S1.3, select cross-linked polyethylene particles with a diameter of 5 mm, dry the cross-linked polyethylene particles at a drying temperature of 100°C and a drying time of 3 hours; heat the extruder to 180°C, add the dried cross-linked polyethylene particles into the hopper of the extruder, push the cross-linked polyethylene particles forward by rotating the screw, the screw speed is 60rpm, the torque is 40N·m, the back pressure is 6MPa, and melt at high temperature;
[0142] The molten cross-linked polyethylene particles are extruded through a die to form a uniform insulating layer 12 which is wrapped around the conductor 11 to obtain a power transmission cable core 1, wherein the overlapping rate of the insulating layer 12 is 30%;
[0143] S1.4, preheat the silicone rubber at 80°C for 30 minutes, inject it into the mold, and then put the conductor and the insulating layer wrapped with the filling material into the mold, and heat it at 180°C for 3 hours to cure the silicone rubber to form a uniform water-blocking and flame-retardant layer 3 with an overlap rate of 30%, which is wrapped around the power transmission cable core 1;
[0144] S1.5. Select a polyurethane foaming agent with a foaming rate of 40 times as the filling material 2, inject it into the water-blocking and flame-retardant layer 3 through a special glue injection gun, and let the foam expand naturally and completely solidify;
[0145] S1.6. Use an electric stirrer to mix the epoxy resin and phthalic anhydride curing agent evenly at a speed of 300 rpm for 30 minutes until the color is consistent and there is no obvious stratification phenomenon. Soak the carbon fiber cloth in the mixed resin to ensure that each fiber is completely soaked in the resin to obtain the armor layer 4. Use a spiral winding method to tightly and evenly wrap the resin-impregnated carbon fiber cloth on the water-blocking and flame-retardant layer 3;
[0146] S1.7, selecting polyolefin particles with a particle size of 100 μm, and drying the polyolefin particles at a drying temperature of 80° C. for a drying time of 3 h;
[0147] The extruder is heated to 200°C, and the dried polyolefin particles are added into the hopper of the extruder. The polyolefin particles are pushed forward by the rotation of the screw. The screw speed is 40rpm, the torque is 50N·m, the back pressure is 6MPa, and they are melted at high temperature. The molten polyolefin particles are extruded through the die to form a uniform outer sheath layer 5, which is wrapped around the armor layer 4.
[0148] The composite polythiophene is prepared as follows:
[0149] S1.1, weigh the following raw materials in parts by weight: 60 parts by weight of polythiophene, 5 parts by weight of dodecylbenzenesulfonic acid, 1 part by weight of boron nitride nanosheets, and 15 parts by weight of N-methylpyrrolidone;
[0150] S1.2, polythiophene and dodecylbenzene sulfonic acid were added to N-methylpyrrolidone respectively, and fully dispersed using a magnetic stirrer at a stirring speed of 400 rpm for 1 h to obtain dispersed polythiophene and dodecylbenzene sulfonic acid;
[0151] The dispersed polythiophene was added into dodecylbenzene sulfonic acid at a rate of 20 drops / min, and stirring was continued to ensure uniform mixing. The stirring speed was 600 rpm and the stirring time was 5 h to obtain doped polythiophene;
[0152] S1.3, adding boron nitride nanosheets to N-methylpyrrolidone, and then adding to the doped polythiophene, using ultrasound to disperse, the ultrasonic power is 300 W, the ultrasonic time is 1 hour, and stirring is continued, the stirring speed is 400 rpm, and the stirring time is 3 hours to obtain a mixture;
[0153] S1.4. Wash the mixture with 70% ethanol to remove unreacted dodecylbenzenesulfonic acid and impurities; then dry it at 80°C for 3 hours to obtain composite polythiophene.
[0154] Embodiment 6: A production process of an underground cable based on non-metallic bionic materials and a cable, comprising the following steps:
[0155] The buried cable structure based on non-metallic bionic materials includes, from the inside to the outside, a power transmission cable core 1, a filling material 2, a water-blocking and flame-retardant layer 3, an armor layer 4, and an outer protective tape layer 5; the power transmission cable core 1 includes, from the inside to the outside, a conductor 11 and an insulating layer 12.
[0156] The production process of underground cables based on non-metallic bionic materials includes the following steps:
[0157] S1.1, weigh the following raw materials in parts by weight: 12 parts by weight of composite polythiophene, 45 parts by weight of cross-linked polyethylene particles, 10 parts by weight of polyurethane foaming agent, 15 parts by weight of silicone rubber, 10 parts by weight of carbon fiber cloth, 17 parts by weight of epoxy resin, 15 parts by weight of phthalic anhydride curing agent, and 12 parts by weight of polyolefin particles;
[0158] S1.2, extrude the composite polythiophene through an extruder, set the extruder temperature to 220° C., the screw speed to 50 rpm, and the back pressure to 6 MPa, to prepare a wire to obtain a conductor 11;
[0159] S1.3, select cross-linked polyethylene particles with a diameter of 5 mm, dry the cross-linked polyethylene particles at a drying temperature of 100°C and a drying time of 3 hours; heat the extruder to 180°C, add the dried cross-linked polyethylene particles into the hopper of the extruder, push the cross-linked polyethylene particles forward by rotating the screw, the screw speed is 60rpm, the torque is 40N·m, the back pressure is 6MPa, and melt at high temperature;
[0160] The molten cross-linked polyethylene particles are extruded through a die to form a uniform insulating layer 12 which is wrapped around the conductor 11 to obtain a power transmission cable core 1, wherein the overlapping rate of the insulating layer 12 is 30%;
[0161] S1.4, preheat the silicone rubber at 80°C for 30 minutes, inject it into the mold, and then put the conductor and the insulating layer wrapped with the filling material into the mold, and heat it at 180°C for 3 hours to cure the silicone rubber to form a uniform water-blocking and flame-retardant layer 3 with an overlap rate of 30%, which is wrapped around the power transmission cable core 1;
[0162] S1.5, select a polyurethane foaming agent with a foaming rate of 40 times as the filling material 2, inject it into the water-blocking and flame-retardant layer 3 through a special glue injection gun, and let the foam expand naturally and completely solidify;
[0163] S1.6. Use an electric stirrer to mix the epoxy resin and phthalic anhydride curing agent evenly at a speed of 300 rpm for 30 minutes until the color is consistent and there is no obvious stratification phenomenon. Soak the carbon fiber cloth in the mixed resin to ensure that each fiber is completely soaked in the resin to obtain the armor layer 4. Use a spiral winding method to tightly and evenly wrap the resin-impregnated carbon fiber cloth on the water-blocking and flame-retardant layer 3;
[0164] S1.7, selecting polyolefin particles with a particle size of 100 μm, and drying the polyolefin particles at a drying temperature of 80° C. for a drying time of 3 h;
[0165] The extruder is heated to 200°C, and the dried polyolefin particles are added into the hopper of the extruder. The polyolefin particles are pushed forward by the rotation of the screw. The screw speed is 40rpm, the torque is 50N·m, the back pressure is 6MPa, and they are melted at high temperature. The molten polyolefin particles are extruded through the die to form a uniform outer sheath layer 5, which is wrapped around the armor layer 4.
[0166] The composite polythiophene is prepared as follows:
[0167] S1.1, weigh the following raw materials in parts by weight: 60 parts by weight of polythiophene, 1 part by weight of dodecylbenzenesulfonic acid, 1 part by weight of boron nitride nanosheets, and 15 parts by weight of N-methylpyrrolidone;
[0168] S1.2, polythiophene and dodecylbenzene sulfonic acid were added to N-methylpyrrolidone respectively, and fully dispersed using a magnetic stirrer at a stirring speed of 400 rpm for 1 h to obtain dispersed polythiophene and dodecylbenzene sulfonic acid;
[0169] The dispersed polythiophene was added into dodecylbenzene sulfonic acid at a rate of 20 drops / min, and stirring was continued to ensure uniform mixing. The stirring speed was 600 rpm and the stirring time was 5 h to obtain doped polythiophene;
[0170] S1.3, adding boron nitride nanosheets to N-methylpyrrolidone, and then adding to the doped polythiophene, using ultrasound to disperse, the ultrasonic power is 300 W, the ultrasonic time is 1 hour, and stirring is continued, the stirring speed is 400 rpm, and the stirring time is 3 hours to obtain a mixture;
[0171] S1.4. Wash the mixture with 70% ethanol to remove unreacted dodecylbenzenesulfonic acid and impurities; then dry it at 80°C for 3 hours to obtain composite polythiophene.
[0172] Embodiment 7: A production process of an underground cable based on non-metallic bionic materials and a cable, comprising the following steps:
[0173] The buried cable structure based on non-metallic bionic materials includes, from the inside to the outside, a power transmission cable core 1, a filling material 2, a water-blocking and flame-retardant layer 3, an armor layer 4, and an outer protective tape layer 5; the power transmission cable core 1 includes, from the inside to the outside, a conductor 11 and an insulating layer 12.
[0174] The production process of underground cables based on non-metallic bionic materials includes the following steps:
[0175] S1.1, weigh the following raw materials in parts by weight: 5 parts by weight of composite polythiophene, 45 parts by weight of cross-linked polyethylene particles, 10 parts by weight of polyurethane foaming agent, 15 parts by weight of silicone rubber, 10 parts by weight of carbon fiber cloth, 17 parts by weight of epoxy resin, 15 parts by weight of phthalic anhydride curing agent, and 12 parts by weight of polyolefin particles;
[0176] S1.2, extrude the composite polythiophene through an extruder, set the extruder temperature to 220° C., the screw speed to 50 rpm, and the back pressure to 6 MPa, to prepare a wire to obtain a conductor 11;
[0177] S1.3, select cross-linked polyethylene particles with a diameter of 5 mm, dry the cross-linked polyethylene particles at a drying temperature of 100°C and a drying time of 3 hours; heat the extruder to 180°C, add the dried cross-linked polyethylene particles into the hopper of the extruder, push the cross-linked polyethylene particles forward by rotating the screw, the screw speed is 60rpm, the torque is 40N·m, the back pressure is 6MPa, and melt at high temperature;
[0178] The molten cross-linked polyethylene particles are extruded through a die to form a uniform insulating layer 12 which is wrapped around the conductor 11 to obtain a power transmission cable core 1, wherein the overlapping rate of the insulating layer 12 is 30%;
[0179] S1.4, preheat the silicone rubber at 80°C for 30 minutes, inject it into the mold, and then put the conductor and the insulating layer wrapped with the filling material into the mold, and heat it at 180°C for 3 hours to cure the silicone rubber to form a uniform water-blocking and flame-retardant layer 3 with an overlap rate of 30%, which is wrapped around the power transmission cable core 1;
[0180] S1.5, select a polyurethane foaming agent with a foaming rate of 40 times as the filling material 2, inject it into the water-blocking and flame-retardant layer 3 through a special glue injection gun, and let the foam expand naturally and completely solidify;
[0181] S1.6. Use an electric stirrer to mix the epoxy resin and phthalic anhydride curing agent evenly at a speed of 300 rpm for 30 minutes until the color is consistent and there is no obvious stratification phenomenon. Soak the carbon fiber cloth in the mixed resin to ensure that each fiber is completely soaked in the resin to obtain the armor layer 4. Use a spiral winding method to tightly and evenly wrap the resin-impregnated carbon fiber cloth on the water-blocking and flame-retardant layer 3;
[0182] S1.7, selecting polyolefin particles with a particle size of 100 μm, and drying the polyolefin particles at a drying temperature of 80° C. for a drying time of 3 h;
[0183] The extruder is heated to 200°C, and the dried polyolefin particles are added into the hopper of the extruder. The polyolefin particles are pushed forward by the rotation of the screw. The screw speed is 40rpm, the torque is 50N·m, the back pressure is 6MPa, and they are melted at high temperature. The molten polyolefin particles are extruded through the die to form a uniform outer sheath layer 5, which is wrapped around the armor layer 4.
[0184] The composite polythiophene is prepared as follows:
[0185] S1.1, weigh the following raw materials in parts by weight: 60 parts by weight of polythiophene, 5 parts by weight of dodecylbenzenesulfonic acid, 5 parts by weight of boron nitride nanosheets, and 15 parts by weight of N-methylpyrrolidone;
[0186] S1.2, polythiophene and dodecylbenzene sulfonic acid were added to N-methylpyrrolidone respectively, and fully dispersed using a magnetic stirrer at a stirring speed of 400 rpm for 1 h to obtain dispersed polythiophene and dodecylbenzene sulfonic acid;
[0187] The dispersed polythiophene was added into dodecylbenzene sulfonic acid at a rate of 20 drops / min, and stirring was continued to ensure uniform mixing. The stirring speed was 600 rpm and the stirring time was 5 h to obtain doped polythiophene;
[0188] S1.3, adding boron nitride nanosheets to N-methylpyrrolidone, and then adding to the doped polythiophene, using ultrasound to disperse, the ultrasonic power is 300 W, the ultrasonic time is 1 hour, and stirring is continued, the stirring speed is 400 rpm, and the stirring time is 3 hours to obtain a mixture;
[0189] S1.4. Wash the mixture with 70% ethanol to remove unreacted dodecylbenzenesulfonic acid and impurities; then dry it at 80°C for 3 hours to obtain composite polythiophene.
[0190] Embodiment 8: A production process of an underground cable based on non-metallic bionic materials and a cable, comprising the following steps:
[0191] The buried cable structure based on non-metallic bionic materials includes, from the inside to the outside, a power transmission cable core 1, a filling material 2, a water-blocking and flame-retardant layer 3, an armor layer 4, and an outer protective tape layer 5; the power transmission cable core 1 includes, from the inside to the outside, a conductor 11 and an insulating layer 12.
[0192] The production process of underground cables based on non-metallic bionic materials includes the following steps:
[0193] S1.1, weigh the following raw materials in parts by weight: 12 parts by weight of composite polythiophene, 30 parts by weight of cross-linked polyethylene particles, 5 parts by weight of polyurethane foaming agent, 10 parts by weight of silicone rubber, 5 parts by weight of carbon fiber cloth, 10 parts by weight of epoxy resin, 10 parts by weight of phthalic anhydride curing agent, and 5 parts by weight of polyolefin particles;
[0194] S1.2, extrude the composite polythiophene through an extruder, set the extruder temperature to 220° C., the screw speed to 50 rpm, and the back pressure to 6 MPa, to prepare a wire to obtain a conductor 11;
[0195] S1.3, select cross-linked polyethylene particles with a diameter of 5 mm, dry the cross-linked polyethylene particles at a drying temperature of 100°C and a drying time of 3 hours; heat the extruder to 180°C, add the dried cross-linked polyethylene particles into the hopper of the extruder, push the cross-linked polyethylene particles forward by rotating the screw, the screw speed is 60rpm, the torque is 40N·m, the back pressure is 6MPa, and melt at high temperature;
[0196] The molten cross-linked polyethylene particles are extruded through a die to form a uniform insulating layer 12 which is wrapped around the conductor 11 to obtain a power transmission cable core 1, wherein the overlapping rate of the insulating layer 12 is 30%;
[0197] S1.4, preheat the silicone rubber at 80°C for 30 minutes, inject it into the mold, and then put the conductor and the insulating layer wrapped with the filling material into the mold, and heat it at 180°C for 3 hours to cure the silicone rubber to form a uniform water-blocking and flame-retardant layer 3 with an overlap rate of 30%, which is wrapped around the power transmission cable core 1;
[0198] S1.5, select a polyurethane foaming agent with a foaming rate of 40 times as the filling material 2, inject it into the water-blocking and flame-retardant layer 3 through a special glue injection gun, and let the foam expand naturally and completely solidify;
[0199] S1.6. Use an electric stirrer to mix the epoxy resin and phthalic anhydride curing agent evenly at a speed of 300 rpm for 30 minutes until the color is consistent and there is no obvious stratification phenomenon. Soak the carbon fiber cloth in the mixed resin to ensure that each fiber is completely soaked in the resin to obtain the armor layer 4. Use a spiral winding method to tightly and evenly wrap the resin-impregnated carbon fiber cloth on the water-blocking and flame-retardant layer 3;
[0200] S1.7, selecting polyolefin particles with a particle size of 100 μm, and drying the polyolefin particles at a drying temperature of 80° C. for a drying time of 3 h;
[0201] The extruder is heated to 200°C, and the dried polyolefin particles are added into the hopper of the extruder. The polyolefin particles are pushed forward by the rotation of the screw. The screw speed is 40rpm, the torque is 50N·m, the back pressure is 6MPa, and they are melted at high temperature. The molten polyolefin particles are extruded through the die to form a uniform outer sheath layer 5, which is wrapped around the armor layer 4.
[0202] The composite polythiophene is prepared as follows:
[0203] S1.1, weigh the following raw materials in parts by weight: 60 parts by weight of polythiophene, 5 parts by weight of dodecylbenzenesulfonic acid, 5 parts by weight of boron nitride nanosheets, and 15 parts by weight of N-methylpyrrolidone;
[0204] S1.2, polythiophene and dodecylbenzene sulfonic acid were added to N-methylpyrrolidone respectively, and fully dispersed using a magnetic stirrer at a stirring speed of 400 rpm for 1 h to obtain dispersed polythiophene and dodecylbenzene sulfonic acid;
[0205] The dispersed polythiophene was added into dodecylbenzene sulfonic acid at a rate of 20 drops / min, and stirring was continued to ensure uniform mixing. The stirring speed was 600 rpm and the stirring time was 5 h to obtain doped polythiophene;
[0206] S1.3, adding boron nitride nanosheets to N-methylpyrrolidone, and then adding to the doped polythiophene, using ultrasound to disperse, the ultrasonic power is 300 W, the ultrasonic time is 1 hour, and stirring is continued, the stirring speed is 400 rpm, and the stirring time is 3 hours to obtain a mixture;
[0207] S1.4. Wash the mixture with 70% ethanol to remove unreacted dodecylbenzenesulfonic acid and impurities; then dry it at 80°C for 3 hours to obtain composite polythiophene.
[0208] Comparative Example 1
[0209] The method of Example 2 is adopted to directly use polythiophene and boron nitride nanosheets together to prepare the polythiophene without modifying the polythiophene.
[0210] Comparative Example 2
[0211] The method of Example 2 is adopted to remove the boron nitride nanosheets.
[0212] The present invention is an underground cable based on non-metallic biomimetic materials prepared by composite polythiophene, wherein the performance index inspection standard of the underground cable is as follows:
[0213] DC resistance test: According to GB / T 3048.4-2007, the DC resistance of the cable is measured in an environment with a temperature of (20±5)℃ and a relative humidity not exceeding 85% to evaluate the conductive performance of the conductor.
[0214] Tensile strength: A tensile testing machine is generally used to measure the tensile strength of cable conductors to evaluate their ability to withstand tensile loads and ensure that the cable can withstand a certain amount of tension without breaking during laying and operation.
[0215] Durability: The cable samples are buried in a box filled with a specific soil type to simulate the actual underground environment. After a certain period of time, the cables are dug out to check their tensile strength and changes in DC resistance.
[0216] According to the above standards, the underground cables prepared in the above Examples 1-8 and Comparative Examples 1-2 were tested, and the obtained data are shown in Table 1:
[0217] Table 1 Performance data of the buried cables of Examples 1-8 and Comparative Examples 1-2
[0218]
[0219] It can be seen from Examples 1-4, Example 7 and Comparative Example 1 that when the mass ratio of polythiophene to the dopant gradually increases, the tensile strength of the buried cable gradually increases, and the DC resistance gradually decreases, but when the mass ratio of polythiophene to the dopant reaches a certain value, the tensile strength of the buried cable gradually decreases, and the DC resistance gradually increases. It can be seen that by adjusting the mass ratio of polythiophene to the dopant, the tensile strength and DC resistance of the buried cable can be regulated. As the proportion of the dopant increases, the tensile strength and DC resistance of the buried cable are improved, but excessive improvement may affect the tensile strength and DC resistance of the buried cable;
[0220] An appropriate amount of dopant can introduce lattice distortion, enhance the material's dislocation resistance, and thus improve its tensile strength. However, when the dopant ratio is too high, the lattice structure will become too complex, and more defects may be formed. These defects will become stress concentration points and reduce the overall mechanical properties of the material. Excessive dopants may lead to the formation of a second phase or phase separation, which will weaken the continuity of the matrix material and reduce the material's toughness, thereby affecting the tensile strength. A high proportion of dopants may make the material more difficult to process, such as easily breaking during extrusion or drawing, resulting in uneven mechanical properties of the final product.
[0221] The right amount of dopant can reduce electron scattering by optimizing the microstructure of the material, thereby reducing DC resistance. However, too much dopant will introduce additional impurity atoms or defects. These impurities and defects will increase electron scattering, thereby increasing resistance. The right amount of dopant can refine the grains and improve conductivity. However, excessive dopant will lead to an increase in grain boundaries. The resistivity at the grain boundaries is usually higher than that inside the crystal, thereby increasing the overall resistance. Some dopants will undergo phase changes or other reactions at specific temperatures. These changes may affect the conductive properties of the material.
[0222] Through Example 5, Example 6 and Example 8, combined with Comparative Example 2, it can be seen that when the boron nitride nanosheets are removed, the tensile strength of the buried cable gradually decreases and the DC resistance gradually increases;
[0223] Boron nitride nanosheets, as a reinforcing agent, can be evenly dispersed in the cable material. By forming a strong interface to enhance the mechanical properties of the matrix material, the tensile strength of the cable can be significantly improved. It can also effectively transfer the external load from one area to another, thereby reducing local stress concentration and preventing the generation and expansion of cracks. When the boron nitride nanosheets are removed, this stress transfer mechanism is weakened, resulting in a decrease in tensile strength. The addition of boron nitride nanosheets can refine the grain size and increase the toughness of the material. Grain refinement can increase the yield strength and ductility of the material, thereby improving the overall tensile strength.
[0224] Although boron nitride nanosheets are insulators themselves, they can optimize the electron transmission path in cables by forming a conductive network, which can reduce electron scattering and thus reduce DC resistance; the interface between boron nitride nanosheets and the matrix material can provide additional conductive channels, helping to reduce the overall resistance; boron nitride nanosheets can fill or cover tiny defects in the matrix material, reducing the impact of these defects on electron transmission, increasing electron scattering, and thus increasing resistance.
[0225] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. The production process of underground cables based on non-metallic bionic materials is characterized by: The following steps are involved: S1.1, weigh the following raw materials in parts by weight: 5-20 parts by weight of composite polythiophene, 30-60 parts by weight of cross-linked polyethylene particles, 5-15 parts by weight of polyurethane foaming agent, 10-20 parts by weight of silicone rubber, 5-15 parts by weight of carbon fiber cloth, 10-25 parts by weight of epoxy resin, 10-20 parts by weight of phthalic anhydride curing agent, and 5-20 parts by weight of polyolefin particles; The composite polythiophene is prepared by modifying polythiophene with a dopant and preparing the polythiophene together with boron nitride nanosheets. S1.2, extruding the composite polythiophene through an extruder, wherein the extruder temperature is set to 180-220°C, the screw speed is set to 20-60 rpm, and the back pressure is set to 2-10 MPa, to prepare a wire to obtain a conductor (11); S1.3, select cross-linked polyethylene particles with a diameter of 5 mm, and dry the cross-linked polyethylene particles; heat the extruder to 150-200°C, add the dried cross-linked polyethylene particles into the hopper of the extruder, and push the cross-linked polyethylene particles forward by rotating the screw, and melt them at high temperature; The molten cross-linked polyethylene particles are extruded through a die to form a uniform insulation layer (12) which is wrapped around the conductor (11) to obtain a power transmission cable core (1), wherein the insulation layer (12) has an overlap rate of 20% to 30%. S1.4, after preheating the silicone rubber, inject it into the mold, then put the conductor and the insulating layer wrapped with the filling material into the mold, and heat the silicone rubber to solidify and shape it to form a uniform water-blocking and flame-retardant layer (3) with an overlap rate of 20% to 30%, which is wrapped around the power transmission cable core (1); S1.5, select a polyurethane foaming agent with a foaming rate of 40 times as the filling material (2), inject it into the water-blocking and flame-retardant layer (3) through a special injection gun, and allow the foam to expand naturally and completely solidify; S1.
6. Use an electric stirrer to mix the epoxy resin and the phthalic anhydride curing agent evenly until the colors are uniform and there is no obvious stratification. Soak the carbon fiber cloth in the mixed resin to ensure that each fiber is completely soaked in the resin to obtain an armor layer (4). Use a spiral winding method to tightly and evenly wrap the resin-impregnated carbon fiber cloth on the water-blocking and flame-retardant layer (3). S1.7, select polyolefin particles with a particle size of 100 μm, and dry the polyolefin particles at a drying temperature of 60-100° C. for a drying time of 2-6 hours; The extruder is heated to 180-250°C, and the dried polyolefin particles are added into the hopper of the extruder. The polyolefin particles are pushed forward by the rotation of the screw, the screw speed is set at 20-50rpm, the torque is set at 40-60N·m, the back pressure is set at 2-10MPa, and melted at high temperature; the molten polyolefin particles are extruded through a die to form a uniform outer sheath layer (5) wrapped around the armor layer (4).
2. The production process of the underground cable based on non-metallic bionic materials according to claim 1 is characterized in that: In S1.3, the drying temperature is 80-100° C. and the drying time is 2-4 hours.
3. The production process of the underground cable based on non-metallic bionic materials according to claim 1 is characterized in that: In the S1.3, the screw speed is set at 20-60 rpm, the torque is set at 10-50 N·m, and the back pressure is set at 2-10 MPa.
4. The production process of the underground cable based on non-metallic bionic materials according to claim 1 is characterized in that: In the above S1.5, the preheating temperature of the silicone rubber is set to 60-100°C, and the preheating time is 10-30 minutes; the temperature for heating the silicone rubber to cure is 120-180°C, and the heating time is 1-3 hours.
5. The production process of the underground cable based on non-metallic bionic materials according to claim 1 is characterized in that: In S1.6, the rotation speed of the electric stirrer is set to 200-400 rpm, and the stirring time is 15-30 min.
6. The production process of the underground cable based on non-metallic bionic materials according to claim 1 is characterized in that: The composite polythiophene is prepared as follows: S1.1, weigh the following raw materials in parts by weight: 50-75 parts by weight of polythiophene, 1-10 parts by weight of dopant, 1-10 parts by weight of boron nitride nanosheets, and 10-20 parts by weight of N-methylpyrrolidone; S1.2, respectively add polythiophene and dopant into N-methylpyrrolidone, use magnetic stirrer to fully disperse, stirring speed is 300-500rpm, stirring time is 0.5-1h, obtain dispersed polythiophene and dopant; Add the dispersed polythiophene to the dopant at 20-30 drops / minute, stirring continuously to ensure uniform mixing, to obtain the doped polythiophene; S1.3, adding boron nitride nanosheets to N-methylpyrrolidone, and then adding to the doped polythiophene, using ultrasound to disperse, and continuously stirring at a stirring speed of 400-600 rpm for 1-5 hours to obtain a mixture; S1.
4. Wash the mixture with 50-70% ethanol to remove unreacted dopants and impurities; then dry the mixture to obtain composite polythiophene.
7. The production process of the underground cable based on non-metallic bionic materials according to claim 6 is characterized in that: In S1.2, the continuous stirring speed is 400-800 rpm, and the stirring time is 3-6 h.
8. The production process of the underground cable based on non-metallic bionic materials according to claim 6 is characterized by: In S1.3, the ultrasonic power is set to 200-400W, and the ultrasonic time is 0.5-1h.
9. The production process of the underground cable based on non-metallic bionic materials according to claim 6 is characterized by: In the step S1.4, the drying temperature is 50-80° C. and the drying time is 2-3 hours.
10. The buried cable based on non-metallic bionic materials is characterized by: The buried cable is manufactured by adopting the production process of the buried cable based on non-metallic bionic materials as described in any one of claims 1 to 9, and comprises, from the inside to the outside, a power transmission cable core 1, a filling material 2, a water-blocking and flame-retardant layer 3, an armor layer 4, and an outer protective tape layer 5; the power transmission cable core 1 comprises, from the inside to the outside, a conductor 11 and an insulating layer 12.
Citation Information
Cited By
Preparation process of robot cable
CN121034759A